2020
DOI: 10.1590/s1678-3921.pab2020.v55.01651
|View full text |Cite
|
Sign up to set email alerts
|

Allometric growth of ½ Dorper + ½ Santa Inês lambs slaughtered with different subcutaneous fat thicknesses

Abstract: The objective of this work was to evaluate the allometric growth, the correlation of the cuts with the half carcasses, and the muscularity index of the leg of ½ Dorper + ½ Santa Inês lambs slaughtered with 2.0, 3.0, and 4.0 mm of subcutaneous fat thickness (SFT). Twenty-four non-castrated male lambs were used, being distributed according to their weight into three collective pens. Slaughtering occurred as the lambs reached the SFT predetermined by ultrasound. The half carcasses were weighed, dissected, and sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These results are in agreement with Sabbioni, et al, (37) who reported that the growth coefficient of loin cuts was early growth. Also, Santos, et al, (39) found that the loin proved to be an early growth rate in lambs slaughtered at 33.5 and 42.8kg. While, the growth coefficient of flank cuts in docked lambs is significantly less than one (0.990) indicating that grew at slower rate than the carcass, on the other hand, the b value in undocked lambs was significantly greater than one (1.610) demonstrated high impetus and late maturing tissue.…”
Section: Resultsmentioning
confidence: 93%
“…These results are in agreement with Sabbioni, et al, (37) who reported that the growth coefficient of loin cuts was early growth. Also, Santos, et al, (39) found that the loin proved to be an early growth rate in lambs slaughtered at 33.5 and 42.8kg. While, the growth coefficient of flank cuts in docked lambs is significantly less than one (0.990) indicating that grew at slower rate than the carcass, on the other hand, the b value in undocked lambs was significantly greater than one (1.610) demonstrated high impetus and late maturing tissue.…”
Section: Resultsmentioning
confidence: 93%